Conceptual Model of the Company's Cyber Resilience Elements - Bahmanova, Alona; Lace, Natalja (Journal of systemics, cybernetics and informatics, 2025)
This study is a continuation of the paper from last year's conference "Cyber Risks: Systematic Literature Analysis". The work considered the process and risks of digitalization. As a result, definitions of cyber risks and cyber threats, cyber security and cyber resilience were given, and differences between similar concepts were considered. Also, as a result of the work, gaps in current approaches to small and medium enterprise (SME) cyber resilience were identified. To eliminate these gaps, it is necessary to see the full picture, understand which elements are included in the company's security system from cyber threats and are also able to strengthen its cyber resilience against threats and how it is possible to minimize cyber risks. In this work, an attempt will be made to build a conceptual model of cyber resilience of small and medium enterprises, considering the elements of the model and their interrelations and interdependencies.